DIFFUSION PHENOMENA IN COOLED BRAKE TRIBOSYSTEMS - Volchenko, Oleksandr; Volchenko, Dmytro; Zhuravlev, Dmytro; Andreychikov, Yevhen; Burava, Oleksandr; Vudvud, Oleksandr; Semeniy, Oleksandr (Problems of Friction and Wear, 2025)
The materials of the article show that, based on multifactor analysis, nanofluid models have been proposed that take into account in base fluids: collisions between: nanoparticles and molecules; nanoparticles caused by Brownian motion; thermal diffusion of nanoparticles and their interaction with molecules; formation of percolation trajectories with low heat resistance in the fluid; influence of: interfacial and boundary layers during the separation of solid and liquid phases; effect of surface shells; thin nanolayers; particle clustering. The study of nanofluids is reduced to determining their thermal conductivity coefficient. When assessing diffusion in rotating systems with nanofluids, forces, various flows, motion speeds, gradients, specific volumes, sedimentation, emerging coefficients, and porosity of liquid nanoparticles in the chamber were taken into account. The interaction of nanoparticles in liquid cooling systems is considered, and nanofluid flows under heat exchange conditions in the chamber of the pulley rim cooling system are evaluated. The heat transfer coefficient from both metallic and non-metallic friction elements of band-pad brakes can be increased by creating a developed heat exchange surface (using fins or pulley deflectors, making air intakes in the form of ribs, etc.), as well as by placing turbulators in the brake parts, which can be made in the form of a hole in the flange or a system of holes and channels in the pulley. The location of bellows above the brake band, interacting with the pulley flange and connected to the holes in the brake band and in the friction lining, or confusers, diffusers, vortex tubes in pairs "pulley - lining" or "lining - band section" also intensifies the cooling of the friction unit [1]. The listed design solutions are aimed at changing the thermodynamic parameters of the air circulating between the working parts of the brake and, as a result, increasing the efficiency of natural-forced cooling. However, natural-forced cooling of the friction pairs of the belt-pad brake of drilling winches is not able to provide a temperature regime lower than that permissible for the friction lining materials during the lowering of the drill pipe string into the well, and therefore we will proceed to consider forced air-liquid cooling.